Conceptualising the empowerment of caregivers raising children with developmental disabilities in Ethiopia: a qualitative study - Zsofia Szlamka; Ikram Ahmed; Elisa Genovesi; Mersha Kinfe; Rosa A. Hoekstra; Charlotte Hanlon (BMC, 2023)
Abstract Background Caregivers of children with developmental disabilities (DDs) in Ethiopia experience stigma and exclusion. Due to limited existing services and substantial barriers to accessing care, they often lack support. Caregiver empowerment could help address injustices that hinder their capacity to support their child as they would like. The aim of this study was to explore the meaning and potential role of empowerment for caregivers raising a child with a DD and how empowerment was situated in relation to other priorities in service development. Methods This was a qualitative phenomenological study. Semi-structured interviews were conducted in Amharic and English with caregivers of children with a DD (n = 15), clinicians (n = 11), community-based health extension workers (n = 5), representatives of non-governmental organisations working with families with DDs (n = 17), and representatives of local authorities in health, education, and social care (n = 15). Data were analysed thematically. Results Three main themes were developed: "Barriers to exercising caregivers' agency"; "Whose decision is it to initiate empowerment?"; and "Supporting caregivers through support groups". Caregiver capacity to do what they thought was best for their child was undermined by poverty, a sense of hopelessness, experience of domestic abuse and multiple burdens experienced by those who were single mothers. Caregivers were nonetheless active in seeking to bring about change for their children. Caregivers and professionals considered support groups to be instrumental in facilitating empowerment. Participants reflected that caregiver-focused interventions could contribute to increasing caregivers' capacity to exercise their agency. A tension existed between a focus on individualistic notions of empowerment from some professionals compared to a focus on recognising expertise by experience identified as vital by caregivers. Power dynamics in the context of external funding of empowerment programmes could paradoxically disempower. Conclusion Caregivers of children with DDs in Ethiopia are disempowered through poverty, stigma, and poor access to information and resources. Shifting power to caregivers and increasing their access to opportunities should be done on their own terms and in response to their prioritised needs.